1998
DOI: 10.1021/ic980217i
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Ionization Energies and Electron Affinities of Ions in Solution from Outer-Sphere Charge Transfer Transition Energies

Abstract: Outer-sphere charge transfer (OSCT) transitions are shown to correlate with previously published photoelectron emission threshold energies. From these data it is possible to generate a set of parameters, I(D) and I(A), which define these OSCT energies, where I(D) is identified as the solution phase vertical ionization potential, and I(A) is the solution phase vertical electron affinity. An easy procedure for deriving these data for a wide variety of cations and anions is presented. The application of these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…It is worth pointing out that the results presented are related to those in a recently published paper of Lever and coworkers 12 on calculation of vertical ionization energies and electron affinities of ions in solution from MMCT bands. Indeed, from the procedure established in this paper, it would be possible, at first, to obtain ligand parameters relevant to the ligand influence on redox properties of complexes.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is worth pointing out that the results presented are related to those in a recently published paper of Lever and coworkers 12 on calculation of vertical ionization energies and electron affinities of ions in solution from MMCT bands. Indeed, from the procedure established in this paper, it would be possible, at first, to obtain ligand parameters relevant to the ligand influence on redox properties of complexes.…”
Section: Introductionsupporting
confidence: 70%
“…On the other hand, ∆G Њ Ј is not the variation of free energy in which we are interested in order to obtain the redox potential of the Co 3ϩ/2ϩ couple, that is the free energy of reaction, ∆G Њ. This free energy corresponds to the process (12), while the Separate reactants ground state ∆G Њ Separate products ground state (12) magnitude which appears in eqn. (11), ∆G Њ Ј , is the variation of free energy when the reactants and products are in contact (that is, when they form the precursor complex and the successor complex, respectively, in the terminology used in the context of Marcus' theory).…”
Section: Measuredmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Table 2 summarizes the results for the GFP model system with the anionic chromophore. charge-transfer-to-solvent states in which the electron is transferred from the chromophore to a cavity forming states resembling solvated electrons 78,79 (in finite clusters, one often observes surface states in which the target orbital corresponds to an electron on the surface). In addition to these physical states, one should also be aware of pseudo-continuum states corresponding to the electron detached from the system.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, our recent work combining spectroscopic studies with density functional theory (DFT) modeling has found several excited state properties of ruthenium-(D)/polypyridyl ligand-(A) complex excited states that differ from expectation based on simple limiting models. [19][20][21][22][23][24] Thus, when the donor and 3 acceptor are covalently linked, and since the energy differences between excited states are often not large in heavy metal complexes, theoretical models based on such weak coupling limits can be misleading.…”
Section: Introductionmentioning
confidence: 99%